Pengaruh Metode Pembelajaran Discovery Learning Terhadap Aktivitas Siswa - I Ketut Mahardika; Villa Febianti; Dian Ayu Puspitasari; Akbar Fattah Al Abshor Charisma; Firdha Yusmar; Rizka Elan Fadilah (Peneliti.net, 2022)
This study aims to abserve student learning activities using the Discoverry learning learning model, with thwe consideration that this study seeks to determine the effect of a variable and take a sample of three classes. The subject is the students of SMP Negeri 3 jember. Based on the results of the sampling, it was found that the discovery learning model has a high level of effectiveness in 9th grade students, namely 6 out of 10 or 60%. It can be said that the Discovery Learnung learning model can improve students’ critical thinking skills and affect student learning outcomes and have a positive impact on student development